KEBIJAKAN PENINGKATAN KUALITAS PELAYANAN DAN KINERJA PELAYANAN PUBLIK DI PROVINSI KALIMANTAN TIMUR - man, Tupar (Jurnal Borneo Administrator, 2007)
Government’s commitment and programs to restore public service delivery in the era of extended regional autonomy is being more apparent. One of efforts in improving service quality and performance is to conduct regular appraisal over service providers and district / city governments as a system. Additionally, stimulating programs that enable service providers and government officials to generate innovation in their daily operation are really imperative. Based on such consideration, East Kalimantan Provincial Government has implemented two sorts of public service assessment according to Minister of Administrative Reform Regulation No. 25 and 26 of 2006. This paper offers basic framework of doing such assessment and the findings regarding public service delivery in East Kalimantan region.  Keywords: penilaian kinerja, kompetisi, pelayanan publik, Kalimantan Timur.